Study On The Traffic Impact Of Logistic-Related Land Use - Louis Tan, Pao Chiang (Universiti Sains Malaysia, 2018)
The North Butterworth Container Terminal (NBCT) and four intersections were selected in this study to address the traffic impact of logistic-related land use. The four intersections are NBCT Entrance Intersection (Intersection A), Jalan Heng Choon Thian/Jalan Bagan Luar/Jalan Kampung Gajah Intersection (Intersection B), Lebuhraya Butterworth Kulim/Jalan Siram/Jalan Sungai Nyior Intersection (Intersection C), and Lebuhraya Lingkaran Luar Butterworth/Jalan Chain Ferry/Jalan Perusahaan Intersection (Intersection D). Traffic data was collected at the entry of NBCT and four intersections near to the container terminal. The operation of NBCT is investigated by observation and interview conducted with the management team of Penang Port Sdn. Bhd. The results of analysis provide trip generation and peak hour of NBCT, and the variation in the traffic demand by vehicle types to and from the container terminal. From the data collected, the average process time of heavy lorries at the registration counter of NBCT is 104.8s. During the peak hour, there are 50 heavy lorries queued and waited on the NBCT approach road. The highest trip generated by NBCT is from 1615 hrs to 1715 hrs with the volume of 1697 pcu/hr. From NBCT, 73% of heavy lorries travelled to Intersection B by passing through Intersection A. As the heavy lorries reached Intersection B, 90% of the heavy lorries travelled to Intersection C. 51% of heavy lorries arrived at Intersection C travelled to Intersection D. From the analysis, it shows that high percentage of heavy lorries travelled along route from NBCT to Mak Mandin and Prai industrial area and vice versa. From the capacity analysis, the approach roads at each intersection with high volume of heavy lorries show LOS E and F.